Revolusi Pendidikan Fisika: Meningkatkan Pemahaman Konsep siswa SMA tentang gelombang berdiri melalui ekperimen mictester berbasis smartphone - Medlin Th. Liunokas; Dens E. S. I. Asbanu (Jurnal Penelitian Pendidikan IPA, 2023)
The study aims to test the effectiveness of using the audio analysis software, Mictester, on smartphones in experiments on standing waves in order to improve students' understanding of concepts in high school. The sample consisted of 19 students of 11th grade at State High School 1 SoE. The instrument used was a test sheet of conceptual understanding of standing wave matter. The results show a significant improvement in students' understanding of concepts after the application of Mictester for audio analysis on Android devices/smartphones. Thus, standing wave experiments that utilize Mictesters software for audio analytics can be an alternative in physics learning, replacing conventional experimental equipment such as oscilloscopes, thereby reducing the cost of experiments.